2021
DOI: 10.24176/wasis.v2i2.6432
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Penggunaan Smartphone pada Perilaku Anak Di Desa Muktiharjo Kabupaten Pati

Abstract: The aims of this study are 1) to analyze the impact of smartphone use on children's behavior in Muktiharjo Village, Pati and 2) to analyze the role of parents in smartphone use in children in Muktiharjo Village, Pati.The research was conducted using a qualitative approach with the type of case study research. The research was conducted in Muktiharjo Village, Margorejo District, Pati Regency. The data collection techniques are through observation, interviews, and documentation. Primary data sources were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…On the other hand, it can also affect a child's emotions when a child has been given a smartphone for watching YouTube videos so that when a child is not given a YouTube spectacle a child will get angry and constantly ask for it (Saihu, 2021). This is in line with the opinion of Saraswati et al (2020) were in their research found that the impact of using smartphones for too long on children's behavior is that children will get angry easily and often shout, then also have an impact on children's social behavior such as decreased social skills, and lazy behavior such as lazy children exercising, lazy to play, and lazy to leave the house.…”
Section: Introductionmentioning
confidence: 55%
“…On the other hand, it can also affect a child's emotions when a child has been given a smartphone for watching YouTube videos so that when a child is not given a YouTube spectacle a child will get angry and constantly ask for it (Saihu, 2021). This is in line with the opinion of Saraswati et al (2020) were in their research found that the impact of using smartphones for too long on children's behavior is that children will get angry easily and often shout, then also have an impact on children's social behavior such as decreased social skills, and lazy behavior such as lazy children exercising, lazy to play, and lazy to leave the house.…”
Section: Introductionmentioning
confidence: 55%
“…Students addicted to smartphones tend to prefer to be alone by playing with smartphones rather than socializing with their friends. Furthermore, excessive use of smartphones can also affect the learning process and focus on children's learning because children will tend to be more interested in smartphones than learning (Andriani et al, 2019;Helni & Hidayat, 2021;Khairunnisa, 2023;Saraswati et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Adults and teenagers need these tools in daily life to support their activities, such as communication, entertainment, assignments, and shopping. The use of smartphones wisely will be able to help in lightening one's work (Khairunnisa, 2023;Saraswati et al, 2021). For example, individuals can communicate with someone without having to meet.…”
Section: Introductionmentioning
confidence: 99%
“…Literasi digital dapat menciptakan tatanan masyarakat dengan pola pikir dan pandangan yang kritis dan kreatif. Masyarakat termasuk siswa, tidak mudah termakan oleh isu-isu provokatif, korban informasi hoaks, atau korban penipuan yang berbasis digital (Ali & Setiawan, 2021;Saraswati et al, 2020). Dengan demikian, kehidupan sosial dan budaya masyarakat cenderung menjadi aman dan kondusif.…”
Section: Hasil Dan Pembahasan a Literasi Digitalunclassified